Influence of seed heteromorphy on morphometry, germination, vigor and morphological characterization of Parahancornia fasciculata (Poir) Benoist - ‘Amapá Amargoso’ (Research, Society and Development, 2021)
Parahancornia fasciculata (Poir) Benoist, popularly known as ‘amapá amargoso’, is an important species in popular and pharmacological medicine due to the latex of its trunk, called ‘leite do amapá’. However, studies on seed technology of this species are still incipient. The objective of this work was to evaluate the influence of the tegument color (heteromorphism) on the morphometry, germination, seed vigor and seedling production of P. fasciculata in order to define the seeds that present greater vigor and the substrate that favors germination. For the germination test, the experimental design was completely randomized in a 2x4 factorial in four replications, two types of seed color (yellow and brown) and four types of substrates (sand, vermiculite, sand and vermiculite 1: 1, and sand and vermiculite 2: 1). The brown seeds had a longer length, width and mass of fresh matter compared to yellow seeds, which indicates that brown seeds have a higher level of maturation, in addition to having higher germination percentages under vermiculite, which relates the vigor of the brown seed being favored under the vermiculite. The germination morphology is of the epigeal type, the cotyledons are foliaceous and photosynthetic, the root is axial and pivoting, a hypocotyl of herbaceous consistency, alternating green protophils and broquidodroma venation. The results of this study indicate the importance of the selective use of seeds based on the color of the seed coat to ensure quality and success in the production of seedlings.